Space in Hand and Mind: Gesture and Spatial Frames of Reference in Bilingual Mexico. Issue 12 (14th December 2020) - Marghetis, Tyler; McComsey, Melanie; Cooperrider, Kensy
Abstract: Speakers of many languages prefer allocentric frames of reference (FoRs) when talking about small‐scale space, using words like "east" or "downhill." Ethnographic work has suggested that this preference is also reflected in how such speakers gesture. Here, we investigate this possibility with a field experiment in Juchitán, Mexico. In Juchitán, a preferentially allocentric language (Isthmus Zapotec) coexists with a preferentially egocentric one (Spanish). Using a novel task, we elicited spontaneous co‐speech gestures about small‐scale motion events (e.g., toppling blocks) in Zapotec‐dominant speakers and in balanced Zapotec‐Spanish bilinguals. Consistent with prior claims, speakers' spontaneous gestures reliably reflected either an egocentric or allocentric FoR. The use of the egocentric FoR was predicted—not by speakers' dominant language or the language they used in the task—but by mastery of words for "right" and "left, " as well as by properties of the event they were describing. Additionally, use of the egocentric FoR in gesture predicted its use in a separate nonlinguistic memory task, suggesting a cohesive cognitive style. Our results show that the use of spatial FoRs in gesture is pervasive, systematic, and shaped by several factors. Spatial gestures, like other forms of spatial conceptualization, are thus best understood within broader ecologies of communication and cognition.